1989
DOI: 10.1152/ajpheart.1989.256.5.h1462
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative deterioration of myocardial function after repeated episodes of exercise-induced ischemia

Abstract: To determine whether progressive regional myocardial dysfunction occurs after repetitive episodes of exercise-induced ischemia, 10 dogs were instrumented with ultrasonic microcrystals for determination of regional myocardial wall thickening, circumflex artery electromagnetic flow probes, and hydraulic coronary artery occluders. Dogs performed treadmill exercise in the presence of a coronary artery stenosis, which limited coronary blood flow to control levels. Dogs performed a single 10-min exercise period one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Intradialytic hypotension (IDH) is known to be associated with increased mortality. Given the underlying vulnerability of hibernating myocardium to increases in demand (12) coupled with decreased coronary flow reserve in HD patients, it may be that this adaptive process actually leads to further segmental injury by exacerbating intradialytic instability. This may be one of the reasons that prevalence of heart failure is so high and survival so poor in HD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intradialytic hypotension (IDH) is known to be associated with increased mortality. Given the underlying vulnerability of hibernating myocardium to increases in demand (12) coupled with decreased coronary flow reserve in HD patients, it may be that this adaptive process actually leads to further segmental injury by exacerbating intradialytic instability. This may be one of the reasons that prevalence of heart failure is so high and survival so poor in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the nondialysis population, repeated episodes of demand ischemia and stunning can result in chronic reduction in left ventricular (LV) function (12). This observation led to the hypothesis that repeated episodes of myocardial ischemia leads to a spectrum of disease-encompassing myocardial stunning through to myocardial hibernation (13) and ending in myocardial remodeling and scarring (14).…”
mentioning
confidence: 99%
“…1 Animal studies have shown that repeated brief bouts of ischemia have a cumulative effect on contractility, such that the duration and severity of myocardial stunning greatly exceed those induced by a single ischemic episode. 7,9,25,33,72,73 If regional perfusion is not measured simultaneously with regional contractile function, the protracted but ultimately reversible dysfunction associated with repetitive stunning may mimic myocardial hibernation. 74 With repetitive stunning, regional perfusion should recover while function remains depressed.…”
Section: Repetitive Stunning Versus Hibernationmentioning
confidence: 99%
“…It is becoming clear that processes relating to the dialysis procedure itself are implicated. In the nonuraemic population, recurrent myocardial stunning (resulting from coronary artery disease) contributes to development and progression of myocardial injury resulting in heart failure (6,7). Studies have demonstrated that standard HD induces global and segmental cardiac ischemia (8,9).…”
Section: Introductionmentioning
confidence: 99%